The influence of simulated pressure changes on the behavior of Larimichthys crocea during the deep sea submarine descent of net cages - Tong, Tong; Yang, Xu; Gui, Fukun; Hu, Jiajun; Niu, Shuai; Tang, Lianghao; Huang, Hengda; Jiang, Yucheng (Frontiers in Marine Science, 2024)
In the process of ascending and descending in deep-sea submerging and lifting cage nets, accompanied by changes in water pressure, pressure is one of the crucial environmental factors affecting the physiology and growth of fish. It directly relates to the comfort of farmed fish in the cage, thereby influencing the quality of aquaculture, especially for high-demanding species on the culture environment like the yellow croaker. Investigating the stress level changes exhibited by yellow croaker under environmental pressure variations, understanding the limit tolerance pressure, and its changes, can provide a theoretical basis for the design, application, and increased production of deep-sea submersible cage nets and yellow croaker aquaculture. This study investigated the effects of different submersion depths (0-20 m) and submersion speeds (0.6, 1, 1.3, 2, 4 m/min) on the physiological and physical behaviors of yellow croaker in cage nets. Physiological and physical behavior indicators were used to reflect the behavioral responses of yellow croaker, including skin and visceral injuries, tailbeat frequency, gasping frequency, swimming speed, and tilt angle. Regarding the pressure changes brought about by different cage submersion depths, the research results indicate that with the increase of submersion depth, the external aquaculture environment pressure on yellow croaker increases. At submersion depths of 15 m and 20 m, the average swimming speed of yellow croaker exceeds 0.05 m/s, the tail movement frequency is 1.42 times that of normal pressure, and the gasping frequency exceeds 20%. When the submersion depth reaches 20